The development and critical evaluation of learner thermal comfort protocol for applicability to two primary schools in Mamelodi, City of Tshwane - Vosloo, Pieter Tobias (University of Pretoria, 2015)
Dissertation (MArch(Prof)--University of Pretoria, 2015.